Zastosowanie business intelligence w logistyce - Zygała, Ryszard (Implementing business intelligence in logistics, 2005)
Business Intelligence becomes part of the standard information technology set used by more and more businesses. To effectively manage the logistics processes, managers need to analyze data collected from different sources and transform it into intelligence and knowledge. Business Intelligence tools can significantly help managers in improving the basic logistic functions like supply chain management, transportation management, warehousing, and inventory management. In this paper, the benefits and challenges of implementing BI in logistics are discussed from different perspectives.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 284-294